Development of A Mindfulness Technique Guidebook in the Framework of Cognitive Behavioral Therapy (CBT) Based on Virtual Reality (VR) to Reduce Exam Anxiety in Grade XII High School Students - Sanjaya, Kadek Diego Dwinanda; Putu Ari Dharmayanti (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Test anxiety is a common psychological issue experienced by students, which can negatively affect both their academic achievement and emotional well-being. Innovative intervention strategies are required to help students manage this anxiety effectively. This study aims to develop and evaluate the effectiveness of a Mindfulness Technique Guidebook within the framework of Cognitive Behavioral Therapy (CBT) based on Virtual Reality (VR) as a psychological intervention tool to reduce test anxiety. The research employed a modified 4D development model (Define, Design, Develop, Disseminate) up to the dissemination phase in the form of article publication. The subjects involved included content experts, media experts, practitioners, and students as end users. Data collection techniques consisted of validation questionnaires, observation sheets, and a test anxiety scale. The intervention’s effectiveness was tested using a Single Subject Research (SSR) design with an A-B-A model. The results indicated that the product demonstrated a high level of validity and was significantly effective in reducing test anxiety (p < 0.05). Additionally, the guidebook was deemed practical and feasible for implementation in school counseling services. These findings suggest that technology-based guides using a mindfulness-CBT approach offer an innovative and applicable alternative for supporting students' mental health in educational settings.